Effect of Friction Stir Welding Speed on Mixed the Stir Rings of Dissimilar Aluminum Alloys (2024-6061) - Athaib Mshari, Abdullah (International Journal of Engineering and Technology, 2018)
The research aims to study the speed effect of friction stir welding tool on the process ofinterference between tow Aluminum alloy (2024-6061) and its effect on the microstructure. A group of pieces from both alloy were taken and welded by means of friction stir welding (FSW) with application of different speeds of rotation . The specimen is then tested using photo microscope. The test showed that two region containing onion rings or (loops) as a result of diversity of the tow alloy and formation of these loops in more than one place in the welding region .The high speed of rotation will result in an incomplete defragmentedÂ  loops but softer than the case low speed and the process of mixing and friction will raise the surface temperature which will cause Grain Growth in the bonding region of two alloy especially at high speed of rotation .Â Â